Characterization of Stress Intensity Factors along an Interface Line Approaching the Vertex in Piezoelectric–Brass Bonded Joints - Luangarpa, Chonlada; Koguchi, Hideo (Engineering, Technology & Applied Science Research, 2025)
In piezoelectric-metal bonded structures, stress singularities occur along the material interfaces due to mismatched mechanical and electromechanical properties. This study investigates the development of stress singularities along the interface line approaching the vertex in a three-dimensional bonded structure composed of piezoelectric ceramic layer (PZT-5H) and brass. The developed analytical model incorporates three-real singularity orders, capturing the intricate stress distribution near the junction corner. To characterize both the orders of singularity (λn) and the corresponding stress intensity factors at different points along the interface, a combined numerical framework employing eigenvalue analysis and a conservative area integral is utilized. The results reveal clear variations in the intensity factors as the vertex is approached. The change in the intensity factor for each singular term is distinct, and the behavior deviates significantly from previously reported trends in single singularity cases. The correlation between the intensity factors at the vertex and along the interface line for multi-singularity cases remains unclear and requires further investigation. These findings contribute to a better understanding of the stress behavior in piezoelectric interfaces and offer a methodological foundation for analyzing other bonded structures involving multi-singularity terms.